Elastic therapeutic tape: Do they have the same material properties? - Chuanpis Boonkerd (2018)
© 2016 The Society of Physical Therapy Science. Published by IPEC Inc. [Purpose] Elastic therapeutic tape has been widely used for rehabilitation and treatment of sports injuries. Tapes with different elastic properties serve different treatment purposes with inappropriate tension reducing tape effectiveness. Many tapes are available in the market, but studies on tape properties are limited. The aim of this study was to examine the material properties of elastic therapeutic tape. [Subjects and Methods] Brands of elastic therapeutic tape included KinesioTex®, ATex, Mueller, 3M, and ThaiTape. The Material Testing System Insight® 1 Electromechanical Testing Systems was used to apply a tensile force on elastic therapeutic tape. Ten specimens of each brand were tested. Stress, load, and Young’s modulus at 25%, 50%, 75%, 100%, and maximum point were collected. One-way analysis of variance with post hoc testing was used to analyze tape parameters. [Results] Maximum elongation and Young’s modulus at all percentages were significantly different between brands. There were no differences in maximum load and maximum stress. [Conclusion] Mechanical properties are different for commercial elastic therapeutic tapes. Physiotherapists and other clinicians should be aware of mechanical tape properties to correctly apply kinesio tape.